The pentateuch ; v. 1 - Keil, Johan Karl Friedrich, 1807-1888; Delitzsch, Franz Julius, 1813-1890; Martin, James (Grand Rapids, MI Eerdmans)
Contents : v. 1 : General introduction ; the first book of Moses (Genesis) ; the second book of Moses (Exodus). Includes bibliographical references.
Keywords: Bible. O.T. Pentateuch -- commentaries